Dispositional Predictors of Professional Well-Being in The Context of The Motivational-Value Model - Voitenko, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
Various aspects of professional well-being are mainly explained by organizational factors, therefore, dispositional factors that contribute to employee well-being in a professional context remain insufficiently studied today. The purpose of this study is to empirically verify the presence and nature of the relationship between the individual psychological properties of employees and their professional well-being in the context of the motivational and value model. In accordance with the purpose of this study, a cross-sectional method was applied using the Job Satisfaction Scale (JSS) by Spector, the Utrecht Work Engagement Scale (UWES) by Schaufeli and Becker, the Bergen Work Addiction Scale (BWAS) by Andreassen et al., the Brief Rosenberg Self-Esteem Scale (B-RSES), the short form of the General Self-Efficacy Scale (GSE-6) by Schwarzer and Jerusalem, the Authenticity Scale (AS) by Wood et al., and the Internal–External Locus of Control Short Scale–4 (IE-4) by Kovaleva. The survey participants were 167 Ukrainian higher education teachers. Statistical analysis included correlation analysis, analysis of variance, and comparative analysis of groups using Student's t-test. The results of the study confirmed the predictive capabilities of dispositional factors in predicting professional well-being, in particular indicators of engagement in work processes, self-esteem, self-efficacy, internal locus of control, as well as the negative impact of one of the authenticity indicators   - self-empowerment. Within the motivational and value model of professional well-being, this result is a valuable confirmation of the professional well-being importance in an employee's ability to successfully control and influence the professional environment; confidence in abilities and good knowledge of himself and understanding of  own work-related experiences, which, in aggregate, provides more chances for  own aspirations realization.